Comparing efficacy of intraarticular single crosslinked Hyaluronan (HYAJOINT Plus) and platelet-rich plasma (PRP) versus PRP alone for treating knee osteoarthritis - Shu-Fen Sun (Nature Portfolio, 2021)
Abstract Intraarticular hyaluronan or platelet-rich plasma (PRP) is widely used in the treatment of knee osteoarthritis (OA). The efficacy of combined hyaluronan with PRP remained inconclusive. This study aimed to investigate the efficacy of combined a single crosslinked hyaluronan (HYAJOINT Plus) and a single PRP versus a single PRP in patients with knee OA. In a prospective randomized-controlled trial, 85 patients with knee OA (Kellgren-Lawrence 2) were randomized to receive a single intraarticular injection of HYAJOINT Plus (3 ml, 20 mg/ml) followed by 3 ml PRP (the combined-injection group, N = 43) or a single injection of 3 ml PRP (the one-injection group, N = 42). The primary outcome was the change from baseline in the visual analog scale (VAS) pain (0–00 mm) at 6 months. Secondary outcomes included The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC, Likert Scale), Lequesne index, single leg stance test (SLS), use of rescue analgesics and patient satisfaction at 1, 3 and 6 months. Seventy-eight patients were available for the intention-to-treat analysis at 6 months. Both groups improved significantly in VAS pain, WOMAC, Lequesne index and SLS at each follow-up visit (p < 0.001). Patients receiving a single PRP experienced significantly greater improvements in VAS pain than patients receiving combined injections at 1-month follow-up (adjusted mean difference: − 5.6; p = 0.017). There were no significant between-group differences in several of the second outcomes at each follow-up visit, except the WOMAC-pain and WOMAC-stiffness scores favoring the one-injection group at 1 month (p = 0.025 and p = 0.011). However, at 6-month follow-up, the combined-injection group achieved significantly better VAS pain reduction (p = 0.020). No serious adverse events occurred following injections. In conclusion, either combined injections of HYAJOINT Plus and PRP or a single PRP alone was safe and effective for 6 months in patients with Kellgren-Lawrence 2 knee OA. Combined injections of HYAJOINT Plus and PRP achieved better VAS pain reduction than a single PRP at 6 months. The results indicating a long term benefit effect of a combination of HYAJOINT Plus and PRP in a particular subset of patients with moderate knee OA need to be replicated in larger trials. ClinicalTrials.gov number NCT04315103.